Physiological quality of Gossypium hirsutum L. seeds after the thermal delinting process - França, Pablo Radamés Cabral de; Almeida, Francisco de Assis Cardoso; Silva, Odilon Reny Ribeiro Ferreira da; Jerônimo, Jeane Ferreira (Comunicata Scientiae, 2018)
The removal of lint from cotton seeds is mainly carried out through chemical delinting, but it is an expensive procedure and requires high technology. The objective was to evaluate the physiological quality of Gossypium hirsutum L. seeds delinted by flaming using a thermal delinter prototype. Cotton seeds BRS 286 were flamed in nine settings intensities and compared to chemical delinting and seeds with lint. We analyzed the water content, germination, first count, germination speed index (GSI), length and dry mass of roots and shoots. Using a completely randomized design and the means were compared by Scott-Knott test at 5% probability. In evaluating, the germination percentage did not differ between treatments with chemical and thermal low intensity delinting compared to the control. In vigor tests were observed higher mean values of the chemical treatment to the other treatments, except in GSI test and root dry weight when subjected to thermal delinting of low and medium intensity. The delinting made through the prototype enables efficient results, as well as the chemical delinting with sulfuric acid, without affecting germination and vigor when flamed with low and middle intensity, regardless of the number of active burners.